PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI DAN SISTEM PENGENDALIAN INTERNAL TERHADAP NILAI INFORMASI PELAPORAN KEUANGAN PEMERINTAH DI KOTA KENDARI - La Ode Anto; Santiadji Mustafa; Evan Gerard K (Pascasarjana Universitas Halu Oleo, 2020)
This study aims to determine the effect on human resource competencies, information technology utilization and internal control systems on the value of government financial reporting information. The sample in this study were 60 employees who took part in making financial policies and were involved in the preparation of the Kendari City Government's financial statements. The research instrument used a questionnaire and the analytical method used was multiple linear regression analysis. The results found that human resource competencies, information technology utilization and internal control systems partially and simultaneously had a positive and significant effect on the value of financial reporting information. The better the competence of human resources, information technology utilization and internal control systems, the higher the value of government financial reporting information will be.